Statistical mass function of prestellar cores from the density distribution of their natal clouds - Donkov, Sava; Veltchev, Todor V.; Girichidis, Ph; Klessen, Ralf S. (Astronomy and astrophysics, 2020)
The mass function of clumps observed in molecular clouds raises interesting theoretical issues, especially in its relation to the stellar initial mass function (IMF). We propose a statistical model of the mass function of prestellar cores (CMF), formed in self-gravitating isothermal clouds at a given stage of their evolution. The latter is characterized by the mass-density probability distribution function (ρ-PDF), which is a power-law with slope q. The different molecular clouds are divided into ensembles according to the PDF slope and each ensemble is represented by a single spherical cloud. The cores are considered as elements of self-similar structure typical for fractal clouds and are modeled by spherical objects populating each cloud shell. Our model assumes relations between size, mass, and density of the statistical cores. Out of these, a core mass-density relationship ρ ∝ mx is derived where x = 1/(1 + q). We find that q determines the existence or nonexistence of a threshold density for core collapse. The derived general CMF is a power law of slope - 1 while the CMF of gravitationally unstable cores has a slope (-1 + x∕2), comparable with the slopes of the high-mass part of the stellar IMF and of observational CMFs.
Gesehen am 28.04.2020